HUBUNGAN PENGETAHUAN DENGAN SIKAP BIDAN TENTANG KONSULTASI ONLINE DALAM MENINGKATKAN KUNJUNGAN PELAYANAN ANTENATAL CARE ( ANC ) - Sharifah Diana; Arum Dwi Anjani; Tri Ribut Sulistyawati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
The frequency of prenatal care visits (ANC) is determined by a number of factors, including age, the distance between the home and the independent midwife practice, and boredom during the examination line wait. Online consultations are one approach for increasing prenatal care (ANC) visits. Online consultation is medical services that facilitate communication between patients and midwives via social media platforms like WhatsApp by utilizing technology and electronic information. The researcher employed a questionnaire as the research instrument, which was given to all 19 independent practice midwives in the Batam Kota district. Based on the findings of the bivariate and univariate analysis that were assessed using Chi-Square, specifically (0.0001 <0.05), the results indicated that midwives' attitudes toward online consultation and knowledge were related to an increase in prenatal care service visits (ANC). The research's findings suggest that in addition to allowing technology to more widely personalize midwife branding, midwives need to keep up with technological advancements in order to compete both domestically and globally.